Radiation and inhibition of angiogenesis by canstatin synergize to induce HIF-1α–mediated tumor apoptotic switch - Magnon, Claire; Opolon, Paule; Ricard, Marcel; Connault, Elisabeth; Ardouin, Patrice; Galaup, Ariane; Métivier, Didier; Bidart, Jean-Michel; Germain, Stéphane; Perricaudet, Michel; Schlumberger, Martin (The Journal of Clinical Investigation, 2007)
Tumor radioresponsiveness depends on endothelial cell death, which leads in turn to tumor hypoxia. Radiation-induced hypoxia was recently shown to trigger tumor radioresistance by activating angiogenesis through hypoxia-inducible factor 1–regulated (HIF-1–regulated) cytokines. We show here that combining targeted radioiodide therapy with angiogenic inhibitors, such as canstatin, enhances direct tumor cell apoptosis, thereby overcoming radio-induced HIF-1–dependent tumor survival pathways in vitro and in vivo. We found that following dual therapy, HIF-1α increases the activity of the canstatin-induced αvβ5 signaling tumor apoptotic pathway and concomitantly abrogates mitotic checkpoint and tetraploidy triggered by radiation. Apoptosis in conjunction with mitotic catastrophe leads to lethal tumor damage. We discovered that HIF-1 displays a radiosensitizing activity that is highly dependent on treatment modalities by regulating key apoptotic molecular pathways. Our findings therefore support a crucial role for angiogenesis inhibitors in shifting the fate of radiation-induced HIF-1α activity from hypoxia-induced tumor radioresistance to hypoxia-induced tumor apoptosis. This study provides a basis for developing new biology-based clinically relevant strategies to improve the efficacy of radiation oncology, using HIF-1 as an ally for cancer therapy.